Angiotensin‐Converting Enzyme Inhibitors Used Concomitantly with Insulin Secretagogues and the Risk of Serious Hypoglycemia. Issue 1 (23rd August 2021) - Hee Nam, Young; Brensinger, Colleen M.; Bilker, Warren B.; Flory, James H.; Leonard, Charles E.; Hennessy, Sean
Abstract : Serious hypoglycemia is a major adverse event associated with insulin secretagogues. Previous studies have suggested a potential relationship between angiotensin‐converting enzyme inhibitors (ACEIs) used with sulfonylureas and serious hypoglycemia, and widely used drug compendia warn of this potential drug‐drug interaction. We investigated the association between serious hypoglycemia and concomitant use of ACEIs in patients receiving insulin secretagogues, using the self‐controlled case series design and Medicaid claims data from 5 US states linked to Medicare claims from 1999–2011. The exposure of interest was active prescription for ACEIs during insulin secretagogue or metformin (negative control object drug) episodes. The outcome was hospital presentation for serious hypoglycemia, identified by discharge diagnosis codes in inpatient and emergency department claims (positive predictive value ~ 78–89%). We calculated confounder‐adjusted rate ratios (RRs) and 95% confidence internals (CIs) of outcome occurrence during ACEI‐exposed vs. ACEI‐unexposed time using conditional Poisson regression. The RRs for ACEIs were not statistically elevated during observation time of glipizide (RR, 1.06; CI, 0.98–1.15), glyburide (RR, 1.05; CI, 0.96–1.15), repaglinide (RR, 1.15; CI, 0.94–1.41), or metformin (RR, 1.02; CI, 0.97–1.06); but was modestly elevated with glimepiride (RR, 1.23; CI, 1.11–1.37) and modestly reduced with nateglinide (RR, 0.73; CI, 0.56–0.96). The overall pattern of results do not suggest that ACEIs used with insulin secretagogues were associated with increased rates of serious hypoglycemia, with the possible exception of glimepiride.